Social Support Pada Anak Penderita Penyakit Terminal - Sukmawati, Relung Fajar; Hamida, Nur Amalia; Amalia, Rizka; Nuqul, Fathul lubabin (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2018)
Patients with terminal diseases who die every year are increasing, especially cancer is predicted to increase. Cancer is the second higest reason of death in the age range of children after an accident. Children who are diagnosed with cancer will certainly limit the activities normally carried out by their age. This is because their time is passed a lot to go through the treatment process that is not short. Therefore, children with terminal disease need support from the closest people who accompany them in the treatment process. The purpose of this study was to determine the role of social support in children with terminal disease. This research was conducted at the Syaiful Anwar Malang hospital, precisely the Pavilium building on the IRNA IVÂ  in a special room used to play for terminalâ€™s patient which is managed by the Sahabat Anak Cancer. This research uses a case study approach and involves 3 children with terminal disease as the subject of research. The results showed that the social support provided by care giver was able to foster a spirit of positive future expectations for patients.